Infective endocarditis with anomalous origin of coronary arteries and an abnormal aortic root bulge: A case report - Yang, Guoliang; Lai, Xiaoyue; Liang, Chunshui; Fan, Weijie; Fu, Wanlei; Liu, Zheng; Xia, Hongmei (Frontiers in Cardiovascular Medicine, 2023)
Background: Aortic bulge sign possibly indicates an arterial aneurysm, pseudoaneurysm, aortic dissection, or aortic diverticulum. The aortic diverticulum is a congenital abnormality of the aorta, mainly known as an aneurysmal remnant of the dorsal fourth aortic arch or ducts arteriosus. But the diverticulum of another part of the aorta has rarely been reported. Case summary: We report a case of a 24-year-old male with a history of oral ulcer presented with recurrent hyperpyrexia and chest pain. Echocardiography and computed tomography showed the anomalous origin of the coronary arteries, aortic valve vegetations, and a bulge at the aortic root. The patient then received a Bentall procedure. The aorta and aortic valves were replaced by a valved conduit. The bulge with a normal arterial wall at the aortic root was considered to be a diverticulum. The infective endocarditis was verified as a secondary oral-derived streptococcal infection. The patient was discharged 15 days after surgery. Postoperative echocardiography had no positive findings. Conclusion: Our case report highlights the role of multimodal cardiovascular imaging for the diagnostic work-up of rare disorders, such as the presence of a diverticulum in the aortic root in a patient with endocarditis and anomalous origin of the right coronary artery.